A humanistic oriented redesign of junior high school algebra teaching modules for the industrial revolution 5.0 - Permanda, Saul; Rifat, Mohammad; Yani T, Ahmad; Suratman, Dede (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to redesign junior high school algebra teaching modules by integrating humanistic learning principles that respond to the educational demands of the Industrial Revolution 5.0. Method: A descriptive qualitative approach was employed through systematic document analysis, expert validation, and iterative revision. The data sources consisted of official algebra teaching modules obtained from the Ministry of Education and Culture’s Ruang Pendidikan platform. Data were collected using document analysis sheets, validation questionnaires, and semi-structured interview guidelines. The redesigned modules were evaluated by two mathematics education lecturers and one practicing junior high school teacher. Data analysis was conducted using qualitative descriptive techniques supported by simple quantitative summaries of validation results to ensure consistency and credibility. Findings: The findings indicate that the original teaching modules were predominantly teacher-centered and did not adequately incorporate key humanistic learning components, including exploration, collaboration, feedback, reflection, and learning technology integration. Expert questionnaire and interview results identified several aspects requiring revision, particularly the clarity of learning activity instructions, the design of group-based learning tasks, feedback mechanisms, and the focus of reflection questions. These findings informed the restructuring of the module into a more learner-centered and humanistic-oriented design. Significance: This study contributes a validated procedural framework for redesigning mathematics teaching modules grounded in humanistic learning principles within the context of the Industrial Revolution 5.0. The findings offer practical guidance for teachers and curriculum developers in adapting existing instructional materials into more engaging, reflective, and contextually relevant learning resources.